Kolaborasi Pentahelix dalam Penanganan Sampah: Studi Kasus Peran Pemerintah, Akademisi, Bisnis, Komunitas, dan Media di Kota Kupang - Fry Loli Keluli, Yohanes; Djani, William; Putu Yoga Bumi Pradana, I (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
This study aims to analyze pentahelix collaboration in waste management in Kupang City, East Nusa Tenggara Province. Waste, particularly household waste, has become a serious problem in almost all major cities in Indonesia, including Kupang. The research employs a qualitative approach using in-depth interviews, participatory observation, and document analysis. The findings reveal significant limitations in human resources, transportation facilities, containers, and budget allocation for waste management. Collaboration among stakeholders remains minimal, with the waste management roadmap yet to be widely socialized. Existing legal instruments are limited to MoUs, cooperation agreements, and temporary decrees. Moreover, public awareness of sorting and disposing of waste properly remains low. The novelty of this study lies in highlighting that waste management cannot be addressed solely by the government but requires pentahelix collaboration involving local government, communities, the private sector, media, and academia. The impact of this research is twofold: it exposes systemic weaknesses in waste governance in peripheral regions while underscoring the importance of cross-actor collaboration. The practical recommendations offered include establishing permanent regulations, strengthening infrastructure, ensuring sustainable budget allocation, and promoting environmental literacy, starting from families to educational institutions. Thus, this study not only identifies problems but also provides concrete policy directions for strengthening sustainable waste governance in Kupang City.